The Influence of Intellectual Capital and Corporate Sustainability on Bank Performance: Innovation as a Mediator - Ingrid Susanto; Tarsisius Renald Suganda; Bagas Brian Pratama (Dinasti Review, 2026)
This study aims to examine the effect of Intellectual Capital and Corporate Sustainability on the financial performance of banks in Indonesia with innovation as a mediating variable. The banking sector faces demands not only to achieve profitability but also to maintain business sustainability and governance quality, while previous research results show inconsistencies regarding the direct effects of Intellectual Capital and Corporate Sustainability on financial performance. This study employs a quantitative causality approach with a sample of eighteen commercial banks listed on the Indonesia Stock Exchange during the 2018–2023 period, yielding 68 observations. Secondary data was obtained from annual financial reports and sustainability reports. Data analysis was conducted using partial least squares. The results show that Intellectual Capital has a positive and significant effect on financial performance, as do Corporate Sustainability and innovation. Both Intellectual Capital and Corporate Sustainability have positive and significant effects on innovation. Furthermore, innovation is proven to partially mediate the effect of Intellectual Capital on financial performance and partially mediate the effect of Corporate Sustainability on financial performance. These findings confirm that innovation serves as a crucial transformation mechanism that converts the potential of intangible assets and sustainability commitments into tangible economic value for banks in Indonesia.